THE ROLE OF INFORMATION SYSTEMS IN MAXIMIZING COMPANY PROFIT - Natallios Peter Sipasulta; Aditya Rian Ramadhan; Siti Nurafiah (Asosiasi Dosen Muda Indonesia, 2022)
It is undeniable that every company can be sure that in carrying out its business always aims to get maximum profit or high return, indeed there are types of companies or business entities that are formed to achieve certain targets that are not related to profit achievement, for example non-profit companies. Non-profit companies whose activities focus on, among others, for purposes related to humanity, nature conservation, and others. Specifically related to companies that are generally engaged in selling services and or goods, it can be said that their orientation is to achieve the maximum profit in running their business. When the number of transactions or buying and selling activities is not too much, it is certainly not a big problem for the company to record transactions manually where the data can also be accessed manually to find out the company's performance and profits for a certain period, but if the company has become large, where the number of goods and or services traded has reached a high enough number and at the same time the company's activities are increasingly complex and complicated, so at that time of course the way of recording transactions or company activities manually would no longer be reliable for serve the needs of the company in monitoring the development of the company's performance including recording company profits for a certain period. Holding a better recording process by using a computer-based information system management approach to record, manage, monitor and move the company so that from time to time it can improve company performance and at the same time increase company profits, this is an option that is not an option. undeniable and need to be taken by the company.